(untitled) (E Conference Zone, 2022)
This article was examined the amount of funds allocated by the Public Charitable Foundation “Vaqf” for the improvement of shrines in our country. The article was also studied the impact of these allocations on increasing the volume of domestic and foreign tourists visiting these shrines.